In Situ Quantification of Oil Film Formation and Breakdown in EHD Contacts. Issue 6 (2nd November 2018) - Maruyama, Taisuke; Nakano, Ken
Abstract : A measurement method using electrical impedance has been developed for simultaneous quantifications of the thickness ( h ) and breakdown ratio (α) of oil films in elastohydrodynamic (EHD) contacts. First, based on simplified geometrical and electrical models of EHD contacts, theoretical expressions of h and α were derived as explicit functions of the measured electrical impedance by using the Lambert function. Then, to verify the proposed measurement principle, oil film thickness measurements were conducted by using the electrical method together with the optical interferometry method in a ball-on-disc-type apparatus, which utilized the lubricated contact between a steel ball and a glass disc with a transparent conductive layer (i.e., an indium tin oxide layer). As a result, it was confirmed that the measured h -values obtained by the electrical method agreed well with those obtained by the optical method, under various test conditions with changing the entrainment speed, slide-to-roll ratio, normal load, and viscosity. Besides, it was also confirmed that the measured α-values obtained by the electrical method showed consistent correlations with the film parameter and the friction coefficient. It is hoped that the developed electrical method will be applied to practical metal-to-metal contacts (e.g., the contacts in practical ball bearings) to understand invisible behaviors of oil films in EHD contacts.